Attention speed and anterior cingulate cortex volume in female and male veterans with suicide ideation and attempts - McGlade, Erin C.; Yancey, James R.; Roberts, Keenan E.; Elias, Audrey; Carson, Chelsea; Ma, Jiyoung; Legarreta, Margaret R.; Yurgelun-Todd, Deborah A. (Frontiers in Psychiatry, 2025)
IntroductionAn average of 17.5 Veterans died by suicide each day in 2021, highlighting the importance of research and prevention efforts aimed at suicide risk. Attentional processes have emerged as a possible predictor of suicide behaviors (SB), yet associated neural correlates remain understudied, particularly in the Veteran population.MethodsThe current study examines sustained and selective attention performance as indexed by the Ruff 2 & 7 Selective Attention Test and anterior cingulate cortex (ACC) volume as they relate to SB in Veterans. A subset of Veterans also completed a structural magnetic resonance imaging protocol. Participants were grouped on history of suicidal ideation (SI), suicide attempt (SA), and no SB (HC).ResultsAnalyses from the Ruff 2 & 7 test showed that Veterans with a history of SA performed more slowly on Automatic Detection Speed (ADS) and Controlled Search Speed (CSS) compared to Veterans with SI and no SB. SI and SA group differences on ADS and CSS remained after Bonferroni correction, and CSS differences remained after controlling for depressive and anxious symptoms. There were no between-group differences on Ruff 2 & 7 Accuracy measures. When analyses were divided by sex, males with a history of SA performed more slowly than SI and HC on ADS and more slowly on CSS and Total Speed than males with a history of SI. Results remained significant after controlling for depressive and anxious symptoms. When Bonferroni corrections were applied, males with a history of SA performed more slowly on ADS, CSS, and Total Speed compared to males with a history of SI. Female Veterans with a history of SA performed more slowly than female HC on CSS only; however, these findings were no longer significant after controlling for depressive and anxious symptoms. No significant differences were found between female groups on ADS or Total Speed. Measures of left rostral ACC gray matter (GM) volume for the combined female and male Veteran sample were positively correlated with ADS and CSS scores in HC but not SA. Conversely, right rostral ACC GM volume negatively correlated with ADS and CSS scores in the SA group but not HC. Right rostral ACC white matter volume correlated positively with ADS and CSS in HC.DiscussionThese findings highlight associations between attention speed, ACC volume, and SB even after controlling for acute mood symptoms, in addition to emphasizing the importance of including sex in analyses.